The Many Faces of Human Leukocyte Antigen-G: Relevance to the Fate of Pregnancy - Mette Dahl; Snezana Djurisic; Thomas Vauvert F. Hviid (Journal of Immunology Research)
Pregnancy is an immunological paradox, where fetal antigens encoded by polymorphic genes inherited from the father do not provoke a maternal immune response. The fetus is not rejected as it would be theorized according to principles of tissue transplantation. A major contribution to fetal tolerance is the human leukocyte antigen (HLA)-G, a nonclassical HLA protein displaying limited polymorphism, restricted tissue distribution, and a unique alternative splice pattern. HLA-G is primarily expressed in placenta and plays multifaceted roles during pregnancy, both as a soluble and a membrane-bound molecule. Its immunomodulatory functions involve interactions with different immune cells and possibly regulation of cell migration during placental development. Recent findings include HLA-G contributions from the father and the fetus itself. Much effort has been put into clarifying the role of HLA-G during pregnancy and pregnancy complications, such as preeclampsia, recurrent spontaneous abortions, and subfertility or infertility. This review aims to clarify the multifunctional role of HLA-G in pregnancy-related disorders by focusing on genetic variation, differences in mRNA stability between HLA-G alleles, differences in HLA-G isoform expression, and possible differences in functional activity. Furthermore, we highlight important observations regarding HLA-G genetics and expression in preeclampsia that future research should address.